High performance of sensorless sliding mode control of doubly fed induction motor associated with two multilevel inverters fed by VFDPC_SVM rectifier - Cherifi Djamila; Yahia Miloud (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
A robust sensorless control based on the sliding-mode observer applied to a doubly fed induction motor associated with two three-level NPC-type voltage inverters fed by PWM rectifier with constant switching frequency and without line voltage sensors, is presented in this paper.  Also, we present an improved direct power control with virtual flux (VFDPC_SVM) for the control of three phase rectifier. Simulation results of this proposed system were analyzed using MATLAB environment.